Wednesday

March 4, 2015

March 4, 2015

Posted by **Andrew** on Wednesday, May 15, 2013 at 11:07pm.

- Algebra -
**Steve**, Thursday, May 16, 2013 at 12:17am(4x-43) + (3x+y)i = (2y-x) + (2x+2y+5)i

so, for the two complex numbers above to be equal,

4x-43 = 2y-x

3x+y = 2x+2y+5

(x,y) = (11,6)

xy=66

**Answer this Question**

**Related Questions**

biology - Given the part of the molecule shown below, can the underlined atom ...

math - Consider the following 6 relations on the set of real numbers: A) y=2x&#...

Product of Roots of Sums of Products of Difference - What is the product of all ...

Product of Roots of Sums of Products of Difference - What is the product of all ...

PreCal - Find all real numbers x and y -2x-4-2yi=3x-2i 5x+2yi=-4+2i 5x=-4 so x=-...

Math Proof - Let S be a non-empty subset of the real numbers that is bounded ...

maths - As x,y,z ranges over all possible real numbers, what is the minimum ...

math - The number 27+200−−−√−−−−...

Grade 12 Calculus - Evaluate each of the following. Show all your calculations...

Algebra - All real # x and y that satisfy -2x-1+2yi=4x-5i first step is place ...